PS 17-29 CLINICAL CHARACTERISTICS ASSOCIATED WITH A GREATER BLOOD PRESSURE INCREASE DURING AEROBIC EXERCISE IN PATIENTS WITH CARDIOVASCULAR DISEASES. (September 2016) - Fujimoto, Naoki; Kumagai, Naoto; Dohi, Kaoru; Moriwaki, Keishi; Omori, Taku; Takeuchi, Tetsushiro; Sugiura, Emiyo; Yamada, Norikazu; Ito, Masaaki
Abstract : Objective: Patients with a hypertensive response to exercise may have left ventricular (LV) diastolic dysfunction. However, clinical characteristics of patients who have a greater systolic blood pressure increase (SBP) during aerobic exercise have been still unclear. Design and method: Eighty-seven cardiovascular patients who underwent echocardiography and maximal cardiopulmonary exercise test (CPX) were enrolled. CPX was performed to determine anaerobic threshold and peak oxygen uptake (peak VO2 ) with simultaneous measurements of cardiac output (CO) using an impedance cardiograph device. The increase in SBP per work load during aerobic exercise and that during anaerobic exercise were determined. Patients were stratified into either greater SBP increase during aerobic exercise than anaerobic exercise (AE) or during anaerobic exercise (AN). Hemodynamics during exercise were compared. Clinical characteristics associated with AE were assessed. Results: Forty-nine patients (66 ± 13 yrs, 61% male) were in AE and 38 (57 ± 15 yrs, 79% male) in AN. AE were older and tended to be more diabetic. No differences were observed in LV dimension and ejection fraction, E wave velocity or estimated LV end-diastolic pressure among the two groups. At rest, heart rate, SBP (125 ± 27 vs. 125 ± 21 mmHg), CO, and aortic elastance were similar in two groups. At anaerobic threshold, SBP (162 ± 34 vs. 144 ± 24 mmHg) and aortic elastance were significantly higher in AE than AN, while heart rate and CO were similar in two groups. Peak SBP, CO, and SV were similar in AE and AN, while peak VO2 was lower in AE. Multivariate analyses showed that female, age, diabetes mellitus, and higher brain natriuretic peptide (BNP) were independent determinants of AE. Conclusions: Patients in AE tended to be older female with diabetes mellitus and higher BNP. They could have greater cumulative afterload in their daily life. Thus, strict BP monitoring using ambulatory BP monitoring may be necessary to prevent diseases such as heart failure with preserved ejection.